IDENTIFIKASI FAKTOR-FAKTOR PENYEBAB KECELAKAAN LALU LINTAS DI KABUPATEN MUKOMUKO - Arya Bhakti Wiranata (HUNILA : Jurnal Ilmu Hukum dan Integrasi Peradilan, 2025)
In accordance with the Law of the Republic of Indonesia Number 22 of 2009 Article 1, a traffic accident is defined as an unwanted and unintentional incident on the road involving a vehicle, with or without other road users, which causes casualties and/or material losses. This study aims to analyze the factors that cause traffic accidents in Kaur Regency. The data analysis method used in this study employs a descriptive-analytical approach, namely by describing the conditions and facts occurring in the field according to the research object at the Mukomuko Regional Police Office (Polres Mukomuko), then organizing, elaborating, and analyzing the collected data based on the applicable legal benchmarks. The findings of this study indicate that there are main factors causing accidents originating from humans. The data shows that traffic accidents in Kaur Regency are influenced by several main factors, namely human factors (driver negligence, violation of the law, and the physical condition of the driver), vehicle factors (poorly maintained vehicle conditions), and road and environmental factors (poor road conditions, lack of traffic signs, and weather). The data also revealed that the majority of accident victims are young individuals, especially teenagers and young adults, with the most frequent accident incidents occurring to motorcyclists.